Characterization of Copper Electrodeposition as a New Filling Technique in 316L Stainless Steel Brazing - Jabur, Adnan S. (Basrah Journal for Engineering Sciences, 2009)
The objective of this research is to characterize new technique of copper filler addition to the brazing joints of 316L stainless steel to overcome the wetting problem between them. This technique includes the electrochemical deposition of copper on the stainless steel joint parts to insure optimum coinciding, minimum oxidation during brazing heating, and consequently good wetting and bonding. An evaluation of the present technique and a comparison with traditional one were performed. The samples ware tested to find the shear strength, microhardness, microstructure and x-ray diffractometry. In general, the present new electrodeposited fillers were clearly better than the traditional filler in producing perfect joints with higher shear strength. On the other hand, there was an opportunity of production acceptable joints with electrodeposited fillers under air environment.